The life and times of Jesus the Messiah - Edersheim, Alfred, 1825-1889. (Peabody, Massa., Hendrickson Publishers, 2004)
Provides background information on Palestine in Christ's time and examines every important stage and event in his life from birth to Resurrection.
1. The preparation for the gospel -- The Jewish world in the days of Christ -- the Jewish dispersion in the East -- The Jewish dispersion in the West -- the Hellenists -- origin of Hellenist literature in the Greek translation of the Bible -- character of the Septuagint -- The old faith preparing for the new -- development of Hellenist theology: The Apocrypha, Aristeas, Aristobulus, and the Pseudepigraphic writings -- Philo of Alexandria, the rabbis, and the gospels --
"The reader will note that a reference to the volume and page number of the original edition has been added to the running head of each page throughout the body of this new, updated edition"--Page xix.
"Complete and unabridged in one volume"--from cover
Includes bibliographical references (pages 1071-1076) and indexes.
Keywords: Jesus Christ -- Biography; Jesus Christ -- Biography; Biographies